Identifying the needed knowledge and skills for health education specialists: qualitative study with stakeholders in Saudi Arabia - Samah Alageel; Lamis Al-Sayyari; Sultana A. Alhurishi (Springer, 2023)
Abstract Background Health education specialists play a major role in promoting a healthy lifestyle, preventing, and managing diseases. This study aimed at identifying the needed skills and knowledge of health education specialists with an interest in disease prevention and the transformation of healthcare in Saudi Arabia. Methods This study employed a qualitative case study approach, using focus group interviews. The study was conducted at King Saud University with three different stakeholder groups (alumni, employers, and faculty members) using convenience sampling. Data was analyzed using thematic analysis. Results We have conducted four focus group interviews with a total of 29 participants. We have identified five main themes from the data; Medical and clinical related knowledge and skills, Communication and engagement with the community, Planning and evaluating health programs, Health systems and health policy, and Marketing and technological skills. Participants highlighted the need to respond to the changing demands of the labor market, the different roles of health education specialists, and patient education vs. public education. Counseling and behavior change were viewed as key roles of health education specialists. In addition to the skills needed to create content and conduct research. Furthermore, equipping health education graduates in the fields of digital health and occupational health was viewed as a key factor in improving their employability and readiness for the labor market. Conclusion Study participants identified multiple skills and knowledge gaps which were deemed important to improve the quality of graduates from the health education program. Future studies are recommended to estimate their importance based on the rating of alumni, faculty staff, and employers.